University Readiness Analysis Towards Green Campus: A Case Study Using UI GreenMetric - Nur Alvira Pascawati; Elisabeth Deta Lusiyati; Jati Untari; Dea Putri Ramadanti (Disease Prevention and Public Health Journal, 2023)
Background: Global warming is a problem that attracts the world's attention because of its harmful effects on living things, including in Indonesia. One of the efforts made by the government is to invite universities to play an active role in reducing the impact of global warming through the green campus program. This study aims to analyze the university's readiness for a Green Campus through a case study at Universitas Respati Yogyakarta (UNRIYO). Method: This research uses a descriptive-quantitative method with case studies at Campus 2 UNRIYO. The population is the entire academic community, infrastructure, transportation, and guidelines that are by the Green Campus indicator. Instruments and data analysis using guidelines from UI GreenMetric with observational variables consisting of 6 indicators, namely Setting & Infrastructure (SI), Energy and Climate Change (EC), Waste (WS), Water (WR), Transportation (TR), and Education & Research (ED). Results: The results of the assessment show that UNRIYO on the SI indicator is at a score of 350 (readiness level 23.3%), EC score of 725 (34.5%), WS score of 450 (25% readiness level), TR score of 0, ED score of 425 (19.4% readiness level). Conclusion: These results indicate that UNRIYO is at a level that is less ready to implement Green Campus. The obstacles experienced are: 1) The supervisory function is still weak so the implementation of the green campus is not sustainable. 2) Incompatibility of infrastructure to realize smart building. 3) There is no sanction and appreciation for the practice of Green Campus. 4) Weak only policy support to create a sustainable environment. 5) Less massive Green Campus socialization, 8) Limited human resources in integrating scientific competence with tri dharma towards Green Campus.